2010
DOI: 10.1021/jp106653c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Photoactuation in Single Wall Carbon Nanotube−Nafion Bilayer Composite

Abstract: Cantilevers made of a bilayer composite of single walled carbon nanotubes (SWNTs) deposited onto Nafion exhibit substantial mechanical motion upon exposure to visible or near-infrared light. The kinetics of the tip displacement are studied as a function of SWNT thickness, mass loading, and humidity level. The rate constants strongly depend upon the SWNT layer thickness. During the light-on cycle the absorption of the light by the SWNTs drives the motion while in the light-off cycle the stiffness of the SWNTs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Moreover, CNT torsion and expansion effects have been proposed as key mechanisms behind mechanical actuation, 12 , 53 and our findings are consistent with those models. Mechanical actuation mechanisms were tentatively modeled first as rigid nanotubes suffering orientational order imposed by uniaxially applied strain.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, CNT torsion and expansion effects have been proposed as key mechanisms behind mechanical actuation, 12 , 53 and our findings are consistent with those models. Mechanical actuation mechanisms were tentatively modeled first as rigid nanotubes suffering orientational order imposed by uniaxially applied strain.…”
Section: Resultssupporting
confidence: 92%
“…The theory of bending of bilayers has been developed by Timoshenko [ 5 ] for bimetal strips exposed to temperature changes. However, actuation of bilayers have also been demonstrated with materials that are responsive to other external stimuli such as relative humidity [ 6 , 7 ], pH [ 8 , 9 ], light [ 10 ], or electric fields [ 11 ]. By introducing anisotropy in the response of the single layers, even more complex movements can be generated.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that the same humidity behavior was observed without the addition of the polymer, that is, SWNTs only, deposited onto a PCB and an alumina substrate. The interaction of SWNTs with humidity has been studied by others,27, 28 and some have reported similar observations. Zahab et al29 attributed the conductivity change of SWNTs upon the exposure of H 2 O to a transition from p ‐type to n ‐type behavior at higher humidity levels.…”
Section: Resultsmentioning
confidence: 99%